Optimization Methods, Theory and Applications - Xu, Honglei; Wang, Song.; Wu, Soon-Yi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book presents the latest research findings and state-of-the-art solutions on optimization techniques and provides new research direction and developments. Both the theoretical and practical aspects of the book will be much beneficial to experts and students in optimization and operation research community. It selects high quality papers from The International Conference on Optimization: Techniques and Applications (ICOTA2013). The conference is an official conference series of POP (The Pacific Optimization Research Activity Group; there are over 500 active members). These state-of-the-art works in this book authored by recognized experts will make contributions to the development of optimization with its applications.
Analyzing Human Walking Using Dynamic Optimization -- Rearrangement Optimization Problems Related to A Class of Elliptic Boundary Value Problems -- An Extension of the MOON2/MOON2R Approach to Many-objective Optimization Problems -- Existence of Solutions For Variational-Like Hemivariational Inequalities Involving Lower Semicontinuous Maps -- An Iterative Algorithm for Split Common Fixed-point Problem for Demicontractive Mappings -- On Constraint Qualifications for Multiobjective Optimization Problems with Vanishing Constraints -- A New Hybrid Optimization Algorithm for the Estimation of Archie Parameters -- Optimization of Multivariate Inverse Mixing Problems with Application to Neural Metabolite Analysis -- Exact Regularization, and Its Connections to Normal Cone Identity and Weak Sharp Minima in Nonlinear Programming -- The worst-case DFT filter bank design with subchannel variations.
Keywords: Mathematics; Operations research; Decision making; Software engineering; Mathematical optimization; Mathematics; Optimization; Operation Research/Decision Theory; Software Engineering/Programming and Operating Systems; Electronic books